Service Quality of Tax Consultant Services at Blessing Consultant Office Gorontalo - Tresya Anggraini Sapii; Lisda Van Gobel; Yahya Antu (Penerbit Jurnal Indonesia, 2024)
This study aims to determine the description of the quality of tax consultant services at the Gorontalo Blessing Consultant Office. This type of research is descriptive qualitative approach. Data collection techniques are done through interviews with a number of informants, observation and documentation. The research focus consists of employee capabilities, data reliability, and employee response. The results showed that: 1) The ability of employees of the Gorontalo Blessing Consultant Office in providing services, namely in tax reporting and preparing client financial reports, is still less competent because of the 4 (four) employees in the Blessing Consultant Office, only 1 (one) person has an accounting education background, while the other 3 (three) people have a background in public administration, management and education. 2) The reliability of data reported by Blessing Konsultan Gorontalo employees is still inaccurate, because every year clients will get a letter from the tax office due to problems with client tax reporting. 3) The response of Blessing Konsultan Gorontalo employees in handling complaints from clients related to problems in tax reporting and financial reports is still not good, this is because there are stillsome client problemsthat are usually not resolved immediately. 4) Overall, the quality of tax consultant services at the Gorontalo Blessing Consultant Office is seen from the ability of employees, data reliability and employee response are still not optimal. It is recommended that the overall services provided by Blessing Consultants Gorontalo still need to be further improved to minimize the problems faced by clients.